Study the Effect of the Anabolic Androgen Methandrostenolone on Some Physiological Parameters in Local Male Rabbits - Mohamed Mohsen Khalaf, Jamil K. Wali (Pakistan Journal of Medical & Health Sciences, 2022)
This study amid to detect the effect of anabolic androgenic Methandrostenolone (Dianabol) on the level of liver enzymes, urea and creatinine in addition to its effect on the level of estrogen in local rabbit. In this experiment, we used (30) adult male rabbits, distributed randomly into three groups, each group 10 animals. Control group(C): Animals were dosed with distilled water only. First treatment group (T1):Animals were dosed orally with Methandrostenolone (Dianabol) within a dosing cycle that continued for (8) weeks in an ascending manner: (0.076, 0.152, 0.304, 0.38, 0.456, 0.532, 0.608, 0.684) mg/kg B.W/d. Second treatment group (T2): Animals were administered the same anabolic androgen orally within a course of doses that lasted for (8) weeks in a hierarchical manner:( 0.076, 0.152, 0.304, 0.38, 0.304, 0.152, 0.076, 0.076) mg/kg B.W/d. After the end of the experiment period, the results showed that the level of (AST, ALT, Creatinine, and Estrogen) increased significantly (P≤0.05) compared to the control group, and the level of these parameters increased significantly(P≤0.05) in the first treatment group compared with the second group. As for the level of (ALP and Urea) in the two treatment groups, it increased significantly (P≤0.05) in comparison with the control group, and there were no significant differences (P>0.05) when comparing the level between the two treatment groups. It is inferred from the results of our study that taking (Dianabol) has a clear negative effect on the liver, kidneys and estrogen in male rabbits, and that this effect increases with the increase in the concentration of the dose used. Keywords: Methandrostenolone, Liver enzymes, Kidney parameters, Estrogen and rabbit